HYDROGEOLOGICAL MODEL AND ITS IMPLICATIONS FOR THE DEVELOPMENT OF UNDERGROUND COAL GASIFICATION IN MUSI BANYUASIN DISTRICT, SOUTH SUMATRA - Ghozi, Muhammad
Musi Banyuasin Regency is one of the proven and currently developed potential Underground Coal Gasification (UCG) locations in South Sumatra. The Muara Enim Formation, which is quite widespread in the South Sumatra Basin, contains thick coal with low rank, so a lot of work and publications have been carried out to increase understanding and implement this UCG technology. Hydrogeological aspects play an important role in determining the location, depth and process of UCG, so the aim of this research is to explain the hydrogeological characterization and its implications in determining depth locations, developing gasification process strategies and environmental monitoring plans for UCG. In this study, an analytical study was carried out from four aspects, namely conceptual physical structure, conceptual process structure, spatial variability structure, and equation structure. Correlation of drill holes and rock permeability produces hydrostratigraphic units in the form of aquifers, aquitards and coal seams. The target coal seam for UCG is located at a depth of 250 with a slope towards the southwest to a depth of 300 m, located between the aquitard layers, and has a distance of approximately 40 m to the aquifer layer above it and 10 m below it. Groundwater flows towards the south and southeast of the study area, with an annual recharge of 289 mm/year which contributes to groundwater storage. This hydrogeological model describes the local support system for the target coal seam, groundwater flow patterns which provide information on hydrostatic pressure around the target coal seam are used to determine the location of injection wells and production wells and the direction of gasification. Although this hydrogeological model is limited by data availability, this conceptual model can be equipped with time series MAT observation data to be applied to groundwater flow simulations based on UCG process simulations in the study area in the future.